Sistem Pemungutan, Administrasi dan Perilaku terhadap Peluang Korupsi Pajak - Arifai, Muhammad (Universitas Malikussaleh, 2013)
The purpose of this study is to investigate whether positive or negative relationship between tax collection systems, tax administration and cultural or behavioral with corruption types opportunity on income tax in Indonesia. This study found mixed results, the lower tax collection system significant with the higher internal corruption opportunity. Similarly, the lower culture is positively relationship with the higher external corruption opportunity. However, low tax administration is not significant with higher internal corruption type based on linier regression model. This study has divided type of corruption into internal and external factors. It is suggest that although tax administration is not significant with level of corruption but this factor is important to ensure high quality of DJP services in Indonesia. The findings also show systemic culture in viewing corruption practices in Indonesia. Results also suggest self assessment system can play important role to effective monitoring and responsible to calculate and reported individual income tax.